1994
DOI: 10.1128/iai.62.9.3793-3800.1994
|View full text |Cite
|
Sign up to set email alerts
|

A 48-kilodalton Mycoplasma fermentans membrane protein induces cytokine secretion by human monocytes

Abstract: Mycoplasmafermentans is one of several Mycoplasma species that have been reported to stimulate tumor necrosis factor (TNF) secretion from monocytes. This activity has been associated primarily with the mycoplasma membrane fraction. In this article, we have characterized a membrane protein that stimulates TNF and interleukin 1,B secretion. The TNF-releasing activity partitioned into the Triton X-114 detergent phase, suggesting that the molecule is hydrophobic. The secretion of TNF is elevated in the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 37 publications
3
29
0
Order By: Relevance
“…Our results are in line with several recent publications reporting the upregulation of TNF-␣, IL-1␤, and IL-6 expression after stimulation of monocytes with mycoplasma-derived membrane fractions (16,22,25). Gamma interferon pretreatment of murine peritoneal macrophages was reported to induce large amounts of nitric oxide when the cells were subsequently stimulated with a mycoplasma-derived high-molecular-weightmaterial (MDHM) (22).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results are in line with several recent publications reporting the upregulation of TNF-␣, IL-1␤, and IL-6 expression after stimulation of monocytes with mycoplasma-derived membrane fractions (16,22,25). Gamma interferon pretreatment of murine peritoneal macrophages was reported to induce large amounts of nitric oxide when the cells were subsequently stimulated with a mycoplasma-derived high-molecular-weightmaterial (MDHM) (22).…”
Section: Discussionsupporting
confidence: 92%
“…Also, infections with cell wall-free mycoplasmas may be associated with strong inflammatory reactions. Recently, some reports demonstrated the macrophage-stimulatory activity of mycoplasmas or mycoplasmaderived lipoprotein fractions in vitro (9,16,26), suggesting that mycoplasma lipoproteins may be directly responsible for the induction of cytokines and chemokines. In this study, we used MALP-2, a chemically well defined prototype of a mycoplasma-derived lipopeptide, and investigated in detail the spectrum of inflammatory mediators that were released in response to this compound.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As another interesting finding, we have shown that IgG antibodies present in SF of our patients have a high affinity to certain M. fermentans membrane lipoproteins, including p48 and p29. p48 was recently shown to be an arthritogenic antigen to induce TNFproduction from human monocytes 31 . More interestingly, various Mycoplasma species were shown to have affinity to cartilage, possibly promoting the homing of the bacteria to the joint tissue 32 .…”
Section: Differences In the Specificity To Certain Lipoproteins Detecmentioning
confidence: 99%